Preparation method and application of magnetically recyclable flexible imprinted MOFs (Metal-Organic Frameworks) catalyst

By constructing a flexible molecular imprint layer on the magnetic Fe-based MOFs catalytic center, selective adsorption and degradation of various difficult-to-degrade organic pollutants, and improving the reuse rate of catalysts through magnetic recovery technology, the problem of difficulty in efficiently degrading various organic pollutants and catalysts in the prior art is solved, and efficient and economical water treatment effect is achieved.

CN119857535AActive Publication Date: 2025-04-22SOUTH CHINA UNIV OF TECH
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510173079.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-17
Publication Date
2025-04-22
Estimated Expiration
2045-02-17

AI Technical Summary

Technical Problem

The existing advanced oxidation technology is difficult to efficiently target the degradation of various difficult-to-degradable organic pollutants in wastewater in water treatment, and the existing molecularly imprinted MOFs catalysts are difficult to recover and cannot be reused multiple times.

Method used

Magnetic Fe-based MOFs are used as the catalytic center to construct a flexible molecular imprint layer to achieve selective adsorption and degradation of a variety of similar or similar structural pollutants, and to improve the reuse rate of the catalyst through magnetic recovery technology.

Benefits of technology

It has achieved efficient targeted degradation of a variety of difficult-to-degrade organic pollutants, improved the catalyst recovery efficiency and multiple utilization capabilities, reduced application costs, and enhanced the practical performance of water treatment technology.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119857535A_ABST
    Figure CN119857535A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of water pollution control, and discloses a preparation method and application of a magnetically recyclable flexible imprinted MOFs catalyst. Magnetic Fe-MOFs are used as a substrate, and a precipitation polymerization method is adopted to synthesize the core-shell structure flexible imprinted catalyst. The catalyst has a multi-target adsorption characteristic, can simultaneously and rapidly capture various sulfonamide organic matters in water in a targeted manner, realizes efficient targeted degradation of sulfonamide organic pollutants in water, has a magnetic recovery characteristic, realizes efficient recovery and reutilization of the catalyst through rapid separation from a solution by an external magnetic field, accords with a green and environment-friendly idea, and has a wide application prospect. And the method has a good engineering application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of treating refractory organic pollutants in wastewater by advanced oxidation technology, and specifically relates to a preparation method and application of a magnetically recoverable flexible imprinted MOFs catalyst. Background Art

[0002] Advanced oxidation processes (AOP) are an important means to eliminate water pollution. Oxidants in the advanced oxidation system, such as H2O2 and persulfate (PS), produce reactive oxidative species (ROS) under catalyst activation, which oxidize and degrade organic pollutants in the water into CO2, H2O or other benign products, thereby reducing water pollution. It is worth noting that the existing ROS generation process has a fast release rate, a large amount, a short life cycle (generally <10μs), and a limited transmission distance (generally <90nm). The large amount of ROS generated instantly is directly quenched in the advanced oxidation process before it can fully contact and react with the pollutants. In addition, there are many types of organic pollutants in wastewater. In the advanced oxidation degradation process, ROS attacks organic matter in wastewater non-selectively, resulting in the preferential degradation of close-range and easily degradable organic pollutants, and the removal effect of specific difficult-to-degrade organic pollutants is not ideal. Therefore, how to achieve efficient targeted degradation of difficult-to-degrade organic pollutants in water is of great significance for the in-depth application of advanced oxidation in water treatment technology.

[0003] In recent years, Metal Organic Frameworks (MOFs) as advanced oxidation catalysts are becoming a research hotspot in the environmental field. MOFs contain different organic ligands, nitrogen-containing heterocyclic ligands, carboxylic acid ligands and other structures, which provide a good basis for the functional modification of MOFs. Related studies have reported that a molecular imprinting layer is constructed on the surface of MOFs, and the selective adsorption of surface molecular imprinting and the catalytic synergy of MOFs are used to achieve targeted degradation of specific pollutants. However, the existing molecular imprinting MOFs are all targeted at a single pollutant. When the water body contains multiple low-concentration difficult-to-degrade organic pollutants at the same time, it is impossible to quickly and effectively eliminate them at the same time. In addition, most of the current imprinted MOFs are in powder form, which causes serious loss in the water treatment process, difficulty in recycling, and cannot be reused many times. Considering the synthesis process and synthesis cost of imprinted MOFs, this greatly limits the engineering application of imprinted MOFs in water treatment processes. Summary of the invention

[0004] In order to overcome the single selectivity and difficult recycling characteristics of existing imprinted MOFs, the purpose of the present invention is to provide a synthesis method and application of existing magnetically recyclable flexible imprinted MOFs catalysts. First, a magnetic MOFs catalytic center is synthesized, and a molecular imprinting layer with a flexible effect is constructed on its surface, which can selectively adsorb multiple pollutants of the same type or with similar structures at the same time, thereby achieving efficient magnetic recycling of imprinted MOFs and selective degradation of multi-target pollutants. This greatly improves the practical performance of imprinted MOFs and is easy to be used in engineering.

[0005] The present invention is achieved through the following technical solutions.

[0006] A method for preparing a magnetically recoverable flexible imprinted MOFs catalyst comprises the following steps:

[0007] (1) Preparation of magnetic Fe-based MOFs catalytic center donor: FeCl3·6H2O and 2-aminoterephthalic acid were added to N,N-dimethylformamide (DMF) solvent and stirred for 30-60 minutes. Then Fe3O4 was added and ultrasonically dispersed for 10-30 minutes. The prepared mixture was transferred to a polytetrafluoroethylene-lined autoclave reactor and heated at 100-150°C for 18-22 hours. The product was washed with DMF, methanol and water respectively, purified and vacuum dried for 24-48 hours, and the obtained product was a magnetic Fe-based MOFs catalytic center donor.

[0008] (2) Preparation of flexible imprinting layer: first, the template molecule, functional monomer and cross-linking agent are added to the reaction solvent and mixed evenly, then the magnetic Fe-based MOFs catalytic center donor is added and ultrasonically dispersed, and the reaction mixture is allowed to stand for 8-16 hours to allow prepolymerization to obtain a prepolymer solution.

[0009] (3) Add an initiator to the prepolymer solution obtained in step (2), and introduce an inert gas for more than 15 minutes to remove oxygen in the solvent. Then, place the solution in a constant temperature oscillating box at 60-65° C. to polymerize the imprinted layer for 8-12 hours. During the polymerization process, the rotation speed needs to be maintained at 220-280 r / min to ensure that the imprinted layer is evenly loaded on the magnetic imprinted MOFs.

[0010] (4) Elution of magnetically recoverable flexible imprinted MOFs catalyst template molecules: The prepolymer obtained in step (3) is first separated by a centrifuge at a speed of 10000-12000 r / min. The obtained solid product is added to a solvent prepared with ethanol and formic acid for Soxhlet extraction, wherein the volume ratio of ethanol to formic acid is 9:1, and then the molecularly imprinted polymer is eluted with ethanol. Finally, the obtained solid product is placed in a vacuum drying oven at 60-80°C for drying, the drying oven temperature is 60-80°C, and the drying time is 24-48h. The obtained product is a magnetically recoverable flexible imprinted MOFs catalyst.

[0011] Furthermore, the hydrothermal synthesis method in step (1) is used to prepare a magnetic iron-based metal organic framework material, specifically: FeCl3·6H2O and 2-aminoterephthalic acid are added to 30mL N,N-dimethylformamide (DMF) in a molar ratio of 2:1-5:1 (preferably 2:1), stirred evenly and transferred to a reactor, and then a certain mass of Fe3O4 is added, the molar ratio of Fe3O4 and 2-aminoterephthalic acid is 5:3-5:9, heated at 110°C for 20h, cooled and washed with DMF, methanol and ultrapure water three times each, and vacuum dried to obtain magnetic Fe-MOFs.

[0012] Furthermore, in step (2), the template molecule of the target pollutant is one or more of sulfamethoxazole, sulfapyridine or sulfamethoxazole.

[0013] Furthermore, in step (2), the functional monomer is one or more of methylenebisacrylamide, methacrylamide, methacrylic acid, 4-vinylpyridine, and methyl acrylate.

[0014] Furthermore, in step (2), the crosslinking agent is one of divinylbenzene, methylenebisacrylamide, ethylene glycol dimethacrylate and trimethylolpropane trimethacrylate.

[0015] Furthermore, in step (2), the volume of the prepolymerization solution is 30-50 ml.

[0016] Furthermore, in step (2), the mass of the added magnetic Fe-MOFs is 0.2-0.5 g, and the mass ratio of the functional monomer to the magnetic Fe-MOFs is 1:1-1:3.

[0017] Furthermore, in step (2), the molar ratio of the template molecule to the functional monomer is 1:3-1:5.

[0018] Furthermore, in step (2), the molar ratio of the functional monomer to the cross-linking agent is 1:1-1:2.

[0019] Furthermore, in step (2), the ultrasonic dispersion time is 15-30 min.

[0020] Furthermore, in step (2), the standing time in the prepolymerization solution is 8-16 hours.

[0021] Furthermore, in step (3), an initiator azobisisobutyronitrile is added.

[0022] Furthermore, in step (3), the mass of the added initiator is 0.05g-0.08g.

[0023] Furthermore, in step (3), the inert gas introduced is nitrogen, and the time for introducing the inert gas is 15-30 minutes.

[0024] Furthermore, in step (3), the polymerization temperature is 60-65°C.

[0025] Furthermore, in step (3), the polymerization time is 8-12 hours.

[0026] Furthermore, in step (3), the rotation speed during the polymerization process is 220-280 r / min.

[0027] Furthermore, in step (4), the rotation speed of the centrifuge is 10000-12000 r / min.

[0028] Furthermore, in step (4), the Soxhlet extraction solvent is ethanol and formic acid in a volume ratio of 9:1.

[0029] Furthermore, in step (4), the drying temperature is 60-80° C. and the drying time is 24-48 hours.

[0030] The present invention also provides that the magnetically recoverable flexible imprinted MOFs catalyst is used in advanced oxidation technology to efficiently remove organic pollutants in wastewater, and the flexible imprinted catalyst based on magnetic Fe-based MOFs is added to wastewater containing organic pollutants, and then an oxidant is added, and the mixture is placed in a constant temperature shaking incubator for shaking reaction, and the reaction temperature is 20-40°C.

[0031] Furthermore, the organic pollutant is a sulfonamide antibiotic.

[0032] Furthermore, the sulfonamide antibiotics include sulfamethoxazole (SMX), sulfapyridine (SPD) and sulfamethoxazole (SMZ).

[0033] Furthermore, the advanced oxidation technology is a persulfate system or a H2O2 system.

[0034] Furthermore, the oxidant is persulfate or H2O2.

[0035] Furthermore, the molar ratio of the sulfonamide organic pollutant to the oxidant is 50:1-150:1, the concentration of the magnetic MOFs-based flexible imprinting catalyst in organic wastewater is 0.1 g / L-1 g / L, and the concentration of organic micropollutants in wastewater is 20 mg / L-50 mg / L.

[0036] The present invention provides a flexible imprinted MOFs of magnetic Fe-MOFs prepared by the above method. The catalyst will be used to solve the problem of difficulty in removing sulfonamide organic pollutants in the process of deep treatment of wastewater.

[0037] The flexible imprinted MOFs catalyst based on Fe-based MOFs provided by the present invention has the following advantages:

[0038] (1) The present invention uses magnetic Fe-based MOFs as a catalytic substrate to achieve rapid magnetic recovery of imprinted MOFs, reduce the loss of imprinted MOFs, and reduce the application cost.

[0039] (2) The imprinted layer of the present invention has certain relaxation properties and can selectively identify sulfonamide organic compounds of the same type or with similar structures, greatly improving the application scenarios of imprinted MOFs in water treatment of organic pollutants.

[0040] (3) The synthetic method of flexible imprinted MOFs based on magnetic Fe-MOFs proposed in the present invention has simple equipment, mild reaction conditions, easy process control, no need to add toxic and harmful reagents, and is convenient for the industrialization of the catalyst. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 This is a performance diagram of flexible imprinted MOFs in adsorbing different sulfonamide organic pollutants.

[0042] Figure 2 This is a comparison chart of the selective adsorption effect of flexible imprinted MOFs on organic micropollutants with different structures.

[0043] Figure 3 STEM image of flexible imprinted MOFs.

[0044] Figure 4 XRD patterns of flexible imprinted MOFs and substrate MOFs.

[0045] Figure 5 Hysteresis curves of flexible imprinted MOFs and substrate MOFs.

[0046] Figure 6 Nitrogen adsorption and desorption spectra of flexible imprinted MOFs and substrate MOFs.

[0047] Figure 7 This is the pore size distribution map of flexible imprinted MOFs and substrate MOFs. DETAILED DESCRIPTION

[0048] The specific implementation of the present invention is further described below in conjunction with examples, but the implementation and protection of the present invention are not limited thereto. It should be noted that if there are processes that are not particularly described in detail below, they can be implemented or understood by those skilled in the art with reference to the prior art. If the manufacturer of the reagents or instruments used is not indicated, they are deemed to be conventional products that can be purchased commercially.

[0049] Example 1

[0050] (1) Preparation of magnetic MIL101-M: 1.35 g FeCl2·6H2O and 0.45 g 2-aminoterephthalic acid were weighed and added to 30 mL DMF. The mixture was stirred for 30 minutes until well mixed, and then 0.72 g Fe3O4 was added. The mixture was poured into a 100 mL polytetrafluoroethylene-lined reactor and placed in an electric constant temperature forced air drying oven preheated to 110°C. After 20 hours, the reactor was taken out and naturally cooled to room temperature. The solid and liquid were separated by filtration or centrifugation, and the solid was washed three times with DMF, methanol and ultrapure water respectively. Finally, the solid was dried in an oven at 60°C to obtain magnetic MIL101-M.

[0051] (2) Preparation of flexible imprinted MOFs: Weigh 0.253 g of sulfamethoxazole (SMX) as a template molecule, add 0.617 g of functional monomer MBA into 45 ml of ethanol (porogen) and stir to mix evenly, then add 0.20 g of MIL101-M prepared in step (1), ultrasonically disperse for 15 min, let stand for 12 h, add 0.754 ml of ethylene glycol dimethacrylate (EGDMA), stir for 30 min, pass N2 for 30 min to exclude oxygen, and let stand for 12 h to form a prepolymer solution.

[0052] (3) Add 0.05 g of azobisisobutyronitrile (AIBN) to the prepolymer solution of step (2), purge with N2 for 30 min, place in a 60°C shaker at 250 r / min for 8 h, and centrifuge to obtain a polymer. Elute the polymer with a mixed solvent Soxhlet extraction method of ethanol / formic acid (v / v=9:1) for more than 12 h to break the bond between the template molecule and the imprinting cavity in the polymer. Wash with anhydrous ethanol and ultrapure water for 3 times respectively to elute the template molecule cleanly, centrifuge, and dry the obtained material at 60°C for 12 h to obtain the flexible imprinted MIL101@MIP-E1.

[0053] (4) Prepare 20 mg / L refractory organic matter solution for standby use;

[0054] (5) A 250 mL conical flask was used as a reactor, 100 mL of sulfamethoxazole (SMX) solution was added, 0.5 g / L of MIL101@MIP-E and 0.074 g / L of PMS were added to the reactor, and the reactor was placed in a shaker at 180 rpm to carry out the degradation reaction at room temperature and in the dark.

[0055] Example 2

[0056] (1) Preparation of magnetic MIL101-M: 1.35 g FeCl2·6H2O and 0.45 g 2-aminoterephthalic acid were weighed and added to 30 mL DMF. The mixture was stirred for 30 minutes until well mixed, and then 0.72 g Fe3O4 was added. The mixture was poured into a 100 mL polytetrafluoroethylene-lined reactor and placed in an electric constant temperature forced air drying oven preheated to 110°C. After 20 hours, the reactor was taken out and naturally cooled to room temperature. The solid and liquid were separated by filtration or centrifugation, and the solid was washed three times with DMF, methanol and ultrapure water respectively. Finally, the solid was dried in an oven at 60°C to obtain magnetic MIL101-M.

[0057] (2) Preparation of flexible imprinted MOFs: Weigh 0.506 g of sulfamethoxazole (SMX) as a template molecule, add 0.617 g of functional monomer MBA into 45 ml of ethanol (porogen) and stir to mix evenly, then add 0.20 g of MIL101-M prepared in step (1), ultrasonically disperse for 15 min and let stand for 12 h, add 0.376 ml of ethylene glycol dimethacrylate (EGDMA), stir for 30 min, pass N2 for 30 min to exclude oxygen, and let stand for 12 h to form a prepolymer solution.

[0058] (3) Add 0.05 g of azobisisobutyronitrile (AIBN) to the prepolymer solution of step (2), purge with N2 for 30 min, place in a 60°C shaker at 250 r / min for 8 h, and centrifuge to obtain a polymer. Elute the polymer with a mixed solvent of ethanol and formic acid (v / v = 9:1) Soxhlet extraction for more than 12 h to break the bond between the template molecule and the imprinting cavity in the polymer. Wash with anhydrous ethanol and ultrapure water for 3 times respectively to elute the template molecule cleanly, centrifuge, and dry the obtained material at 60°C for 12 h to obtain the flexible imprinted MIL101@MIP-E2.

[0059] Example 3

[0060] (1) Preparation of magnetic MIL101-M: 1.35 g FeCl2·6H2O and 0.45 g 2-aminoterephthalic acid were weighed and added to 30 mL DMF. The mixture was stirred for 30 minutes until well mixed, and then 0.72 g Fe3O4 was added. The mixture was poured into a 100 mL polytetrafluoroethylene-lined reactor and placed in an electric constant temperature forced air drying oven preheated to 110°C. After 20 hours, the reactor was taken out and naturally cooled to room temperature. The solid and liquid were separated by filtration or centrifugation, and the solid was washed three times with DMF, methanol and ultrapure water respectively. Finally, the solid was dried in an oven at 60°C to obtain magnetic MIL101-M.

[0061] (2) Preparation of flexible imprinted MOFs: Weigh the sulfamethoxazole template molecule and the functional monomer MBA in the amounts shown in Table 1, add them into 30 ml of ethanol (porogen), stir and mix evenly, then add 0.20 g of MIL101-M prepared in step (1), ultrasonically disperse for 15 min, let stand for 12 h, add ethylene glycol dimethacrylate (EGDMA) in the amount shown in Table 1, stir for 30 min, pass N2 for 40 min to exclude oxygen, and let stand for 12 h to form a prepolymer solution.

[0062] (3) Add 0.05 g of azobisisobutyronitrile (AIBN) to the prepolymer solution of step (2), purge with N2 for 30 min, place in a 60°C shaker at 250 r / min for 12 h, and centrifuge to obtain a polymer. Elute the polymer with a mixed solvent of ethanol and formic acid (v / v = 9:1) Soxhlet extraction for more than 12 h to break the bond between the template molecule and the imprinting cavity in the polymer. Wash with anhydrous ethanol and ultrapure water for 3 times respectively to elute the template molecule cleanly, centrifuge, and dry the obtained material at 60°C for 12 h to obtain different flexible imprinted MOFs.

[0063] Based on the synthesis conditions of flexible imprinted MOFs, the detailed synthesis control conditions are shown in Table 1:

[0064] Table 1

[0065]

[0066] Example 4

[0067] (1) Preparation of magnetic MIL101-M: 1.35 g FeCl2·6H2O and 0.45 g 2-aminoterephthalic acid were weighed and added to 30 mL DMF. The mixture was stirred for 30 minutes until well mixed, and then 0.72 g Fe3O4 was added. The mixture was poured into a 100 mL polytetrafluoroethylene-lined reactor and placed in an electric constant temperature forced air drying oven preheated to 110°C. After 20 hours, the reactor was taken out and naturally cooled to room temperature. The solid and liquid were separated by filtration or centrifugation, and the solid was washed three times with DMF, methanol and ultrapure water respectively. Finally, the solid was dried in an oven at 60°C to obtain magnetic MIL101-M.

[0068] (2) Preparation of flexible imprinted MOFs: Weigh 0.506 g of sulfamethoxazole (SMX) as a template molecule, add 0.617 g of functional monomer MBA into 30 ml of ethanol (porogen) and stir to mix evenly, then add 0.20 g of MIL101-M prepared in step (1), ultrasonically disperse for 15 min and let stand for 12 h, add 0.376 ml of ethylene glycol dimethacrylate (EGDMA), stir for 30 min, pass N2 for 30 min to exclude oxygen, and let stand for 12 h to form a prepolymer solution.

[0069] (3) Add 0.1 g of azobisisobutyronitrile (AIBN) to the prepolymer solution of step (2), purge with N2 for 30 min, place in a shaker at 80°C and stir at 100 r / min for 20 h until the reaction is complete, centrifuge to obtain a polymer, and elute the polymer with a mixed solvent of ethanol and formic acid (v / v = 9:1) Soxhlet extraction for more than 12 h to break the bond between the template molecule and the imprinting cavity in the polymer. Then wash with anhydrous ethanol and ultrapure water for 3 times respectively to elute the template molecule cleanly, centrifuge, and dry the obtained material at 60°C for 12 h to obtain MIL101@MIP-E2.

[0070] Comparative Example 1

[0071] (1) Preparation of magnetic MIL101-M: 1.35 g FeCl2·6H2O and 0.45 g 2-aminoterephthalic acid were weighed and added to 30 mL DMF. The mixture was stirred for 30 minutes until well mixed, and then 0.72 g Fe3O4 was added. The mixture was poured into a 100 mL polytetrafluoroethylene-lined reactor and placed in an electric constant temperature forced air drying oven preheated to 110°C. After 20 hours, the reactor was taken out and naturally cooled to room temperature. The solid and liquid were separated by filtration or centrifugation, and the solid was washed three times with DMF, methanol and ultrapure water respectively. Finally, the solid was dried in an oven at 60°C to obtain magnetic MIL101-M.

[0072] (2) Preparation of MIL101@NIP-E1: Without adding sulfamethoxazole (SMX) as a template molecule, 0.617 g of the functional monomer MBA was added to 45 ml of ethanol and stirred to mix evenly. Then, 0.20 g of MIL101-M prepared in step (1) was added, and ultrasonic dispersion was performed for 15 min, followed by standing for 12 h. 0.754 ml of ethylene glycol dimethacrylate (EGDMA) was added and stirred for 30 min. N2 was introduced for 30 min to exclude oxygen, and the mixture was allowed to stand for 12 h to form a prepolymer solution.

[0073] (3) Add 0.05 g of azobisisobutyronitrile (AIBN) to the prepolymer solution of step (2), purge with N2 for 30 min, place in a 60°C shaker at 250 r / min for 8 h, and centrifuge to obtain a polymer. Elute the polymer with a mixed solvent Soxhlet extraction method of ethanol / formic acid (v / v=9:1) for more than 12 h to break the bond between the template molecule and the imprinting cavity in the polymer. Wash with anhydrous ethanol and ultrapure water for 3 times respectively to elute the template molecule cleanly, centrifuge, and dry the obtained material at 60°C for 12 h to obtain the flexible imprinted MIL101@NIP-E1.

[0074] Application Example 1

[0075] Application Example 1 explores the adsorption performance of Example 1 on different Sas pollutants

[0076] Sulfadimethoxazole (SMX), sulfapyridine (SPD), and sulfathiazole (SMZ) were selected as typical representatives of SAs pollutants, that is, the prepared solution (the solvent is water) was used to explore the SMX adsorption performance of MIL101@MIP-E1 prepared in Example 1. The concentration of each pollutant was 50 mg / L. 0.06 g of MIL101@MIP-E1 and MIL101@NIP-E1 catalysts were added to 100 mL of the above mixed solution, and the reaction solution was placed in a constant temperature shaking incubator with the rotation speed controlled at 180 rpm and the temperature at 25°C. After adsorption equilibrium (12 hours), sampling was carried out to detect the adsorption capacity of the catalyst for different pollutants. The adsorption capacity of the above four catalysts for different pollutants is as shown below. Figure 1 As shown in the figure, the adsorption capacity of MIL101@MIP-E1 for SMX can reach 32.96 mg / g, the adsorption performance for SPD can reach 28.18 mg / g, and the adsorption capacity for SMZ can reach 26.13 mg / g, which indicates that MIL101@MIP-E1 has good adsorption performance for SAs pollutants with the same structure. In addition, the adsorption capacity of MIL101@MIP-E1 for MIL101@NIP-E1 is higher, indicating that it has a good template effect.

[0077] Application Example 2

[0078] Application Example 2 explores the selective adsorption performance of Example 1 in mixed water.

[0079] Pollutants with different structures, namely sulfamethoxazole (SMX), phenol (PhOH), ciprofloxacin (CIP) and tetracycline (TET), were selected to prepare a mixed solution (the solvent was water) to explore the selective adsorption performance of MIL101@MIP-E1 prepared in Example 1. The concentration of each pollutant was 20 mg / L. 0.06 g of MIL101@MIP-E1 and MIL101@NIP-E1 catalysts were added to 100 mL of the above mixed solution, and the reaction solution was placed in a constant temperature shaking incubator with the rotation speed controlled at 180 rpm and the temperature at 25°C. After adsorption equilibrium (12 hours), sampling was carried out to detect the adsorption capacity of the catalyst for different pollutants. The adsorption capacity of the above four catalysts for different pollutants is as follows. Figure 2 As shown, the adsorption capacity of MIL101@MIP-E1 for the target pollutant SMX can reach 21.38 mg / g, which is 1.71 times that of MIL101@NIP-E1. This shows that the imprinted pore catalyst prepared in Example 1 of the present invention has good template performance; in addition, the adsorption capacity of MIL101@MIP-E1 for CIP, TCH and PhOH is 7.02 mg / g, 14.1 mg / g and 7.8 mg / g, respectively, which are far lower than the adsorption capacity of SMX, indicating that it has good selective adsorption performance in mixed water.

[0080] Application Example 3

[0081] Application Example 3 compares the effects of different catalyst concentrations on pollutant removal

[0082] This application example compares the effect of the dosage of MIL101@MIP-E1 prepared in Example 1 (0.1g / L, 0.2g / L, 0.4g / L, 0.6g / L, 0.8g / L) on the catalytic activation degradation of SMX. Sodium persulfate was used as the oxidant, and the dosage of sodium persulfate was 0.188g. Four groups of SMX simulated organic wastewater with an initial SMX concentration of 20mg / L were prepared. Without adjusting the pH of the wastewater, a conical flask was used as the reactor, and five treatment groups were set up for the reaction, namely: (1) adding 0.1g / L of MIL101@MIP-E1; (2) adding 0.2g / L of MIL101@MIP-E1; (3) adding 0.4g / L of MIL101@MIP-E1. (4) adding 0.6g / L of MIL101@MIP-E1. (5) Add 0.8 g / L of MIL101@MIP-E1 and add the above four groups of reaction solutions to the conical flask in turn. Stir at room temperature to make the reaction uniform. Place the conical flask in a shaker at 180 rpm and carry out the reaction at room temperature (25°C). Take samples at intervals and use high performance liquid chromatography (HPLC) to determine the residual concentration of SMX in the wastewater and convert it into removal rate. The results are shown in Table 2.

[0083] Table 2

[0084]

[0085]

[0086] As shown in Table 2, as the concentration of the catalyst gradually increases, the removal rate of SMX gradually increases. When the catalyst concentration is 0.8g / L, the maximum removal rate of SMX within 1h reaches 94.25%. When the catalyst concentration increases from 0.4g / L to 0.6g / L, the removal rate increases by 15.5%, and when the catalyst increases from 0.6g / L to 0.8g / L, the removal rate increases by 8.9%. Considering the reaction removal rate and use cost, the 0.6g / L catalyst is the best.

[0087] Application Example 4

[0088] Application Example 4 compares the effects of different pH on pollutant removal

[0089] This application example compares the effect of MIL101@MIP-E1 prepared in Example 1 on the catalytic activation and degradation of SMX under different pH solutions. Sodium persulfate was used as the oxidant, and the dosage of sodium persulfate was 0.188g. Four groups of SMX simulated organic wastewater with an initial SMX concentration of 20mg / L were prepared. The pH of the solution was adjusted using 0.1mM / L hydrochloric acid and sodium hydroxide, and a conical flask was used as a reactor. Four treatment groups were set up for the reaction, namely: (1) adjusting the pH to 3; (2) adjusting the pH to 5; (3) adjusting the pH to 7; (4) adjusting the pH to 9. 0.6g / L of MIL101@MIP-E1 was added to the conical flask in turn, and the reaction was stirred at room temperature to make it uniform. The conical flask was placed in a shaking table at 180rpm and the reaction was carried out at room temperature (25℃). Sampling was performed at intervals, and the residual concentration of SMX in the wastewater was determined by high performance liquid chromatography (HPLC) and converted into removal rate. The results are shown in Table 3.

[0090] Table 3

[0091]

[0092] As shown in Table 3, MIL101@MIP-E1 has the best removal rate of SMX at pH 5, reaching 91.5%. In addition, at different pH values, its removal rate of SMX reached more than 80%, indicating that it has good degradation performance for SMX in a wide pH range.

[0093] Experimental and testing instructions

[0094] The MIL101@MIP-E1 catalyst prepared in Example 1 was characterized. Figure 3-6 shown. Figure 3 This is the STEM image of MIL101@MIP-E1 prepared in Example 1. It can be seen that the molecular imprinting layer is successfully loaded on the MOFs base substrate to form a core-shell structure. Figure 4 The XRD patterns before and after imprinting show that the characteristic peaks after imprinting are consistent with those of the substrate MIL101-E, which indicates that the introduction of the flexible imprinting layer does not affect the crystal structure of the substrate MOFs. Figure 5 The magnetization curves of MIL101-M and MIL101@MIP-E1 prepared in Example 1 show that the hysteresis loop of MIL101-M is S-shaped, indicating that MIL101-M has superparamagnetism. The saturation magnetization of MIL101@MIP-E1 after imprinting decreases from 35.3emu / g to 4.5emu / g, indicating that the imprinting layer weakens the magnetic strength of the catalyst. However, its hysteresis loop still shows an S-shape, which is still sufficient to achieve rapid separation in solution. Figure 6 and Figure 7 The N2 adsorption-desorption isotherms and pore size distribution curves of MIL101-M and MIL101@MIP-E1 are shown in Figure 2. The results show that the specific surface area after imprinting increased from 58.89 m 2 / g dropped to 23.07m 2 / g, which may be due to the coverage of the imprint, resulting in a decrease in the specific surface area of ​​the catalyst. The pore size ranges from 0.020cm 3 / g increases to 0.048cm 3 / g. This is beneficial to the mass transfer of oxidants. The pore size distribution results show that after imprinting, micropores of 1.5nm, mesopores of 17.02nm and macropores of 36.97nm were newly formed.

Claims

1. A method for preparing a magnetically recoverable flexible imprinted MOFs catalyst, characterized in that: The steps include: (1) Synthesizing the magnetic Fe-based MOFs catalytic center substrate by hydrothermal method: adding ferric chloride hexahydrate and 2-aminoterephthalic acid to N,N-dimethylformamide solvent and stirring to dissolve, then adding Fe3O4 and transferring the prepared mixture to an autoclave reactor and heating, and washing the product with N,N-dimethylformamide, methanol and water respectively and drying to obtain a magnetic Fe-based MOFs catalytic center donor with amino group; (2) firstly adding the template molecule, the functional monomer and the cross-linking agent into the reaction solvent and uniformly dispersing and mixing them by ultrasonic dispersion, then adding the amino-containing magnetic Fe-based MOFs catalytic center donor obtained in step (1), standing for 12-18 hours for full prepolymerization, and obtaining a prepolymer solution; (3) adding an initiator to the prepolymer solution, introducing an inert gas, and heating and stirring to initiate the polymerization reaction of the template molecule, the functional monomer, and the cross-linking agent to form an imprinting layer on the surface of the magnetic Fe-MOFs; (4) The reaction product is subjected to Soxhlet extraction using methanol / acetic acid as an eluent to remove the template molecule, and then washed with methanol, centrifuged, and vacuum dried to obtain magnetically recoverable flexible imprinted MOFs.

2. The method for preparing the magnetically recoverable flexible imprinted MOFs catalyst according to claim 1, characterized in that: In step (1), the molar ratio of Fe3O4 to 2-aminoterephthalic acid is 5:3-5:9, the synthesis temperature of the hydrothermal method is 100-150°C, and the synthesis time is 16-24h; the molar ratio of ferric chloride hexahydrate to 2-aminoterephthalic acid is 2:1-5:

1.

3. The method for preparing the magnetically recoverable flexible imprinted MOFs catalyst according to claim 1, characterized in that: In step (2), the functional monomer is one of methacrylic acid, methylenebisacrylamide, methacrylamide, and methyl methacrylate; the template molecule is one or more of sulfamethoxazole, sulfadiazine, sulfamethoxazole, and sulfathiazole; the cross-linking agent is one or more of ethylene glycol dimethacrylate, divinylbenzene, and ethylene glycol dimethacrylate; the reaction solvent is one of ethanol, methanol, and acetonitrile; and the porogen is the reaction solvent.

4. The method for synthesizing a magnetically recoverable flexible imprinted MOFs catalyst according to claim 1, characterized in that: In step (2), the molar ratio of the functional monomer to the template molecule is 1:1-6:1; the molar ratio of the functional monomer to the cross-linking agent is 4:3-4:5; the molar ratio of the functional monomer to the cross-linking agent is 4:3-4:7; the mass ratio of the functional monomer to the magnetic Fe-based MOFs catalytic center donor is 2:3-3:4; and the porogen is 30-45ml.

5. The method for synthesizing a magnetically recoverable flexible imprinted MOFs catalyst according to claim 1, characterized in that: In step (2), the ultrasonic dispersion time is 15-20 minutes, and the prepolymerization standing time is 12-16 hours.

6. The method for synthesizing a magnetically recoverable flexible imprinted MOFs catalyst according to claim 1, characterized in that: In step (3), the initiator is azobisisobutyronitrile, and the molar ratio of azobisisobutyronitrile:template molecule is 1:3-1:5; the time of passing the inert gas is 15-20 minutes, the polymerization heating temperature is 60-80°C, the rotation speed is 180-300r / min, and the polymerization time is 8-16h; the inert gas is nitrogen; The volume ratio of formic acid / ethanol in the eluent is 5:1-9:1, the elution time is 16-24 hours, the vacuum drying temperature is 60-80°C, and the vacuum drying time is 16-24 hours.

7. A magnetically recoverable flexible imprinted MOFs catalyst prepared by the synthesis method according to any one of claims 1 to 6.

8. The magnetically recyclable flexible imprinted MOFs catalyst of claim 7 is used in advanced oxidation technology to efficiently remove sulfonamide organic pollutants in water, characterized in that: The flexible imprinting catalyst is added into a water body containing sulfonamide antibiotics, and then an oxidant is added to carry out a constant temperature oscillation reaction at a reaction temperature of 20-25°C.

9. The use according to claim 8, characterized in that: The advanced oxidation technology is a persulfate system; the added oxidant is sodium persulfate or potassium hydrogen persulfate.

10. The use according to claim 8, characterized in that: The molar ratio of the dosage of the oxidant to the difficult-to-degrade organic pollutants is 50:1-100:1; the concentration of the flexible imprinted catalyst in the wastewater is 0.1g / L-1.0g / L; the concentration of organic micropollutants in the wastewater is 20mg / L-100mg / L, and the degradation reaction time is 30-60min.

Citation Information

Patent Citations

  • Molecular imprinting type MOFs catalyst and preparation and application thereof in specific catalytic degradation of antibiotics

    CN111892711A

  • MOFs (Metal-Organic Frameworks)-based 3D (Three-Dimensional) nano-imprinted pore

    CN115178241A

  • Fe-N4 active site monatomic catalyst for selectively generating singlet oxygen by activating peroxydisulfate as well as preparation method and application of Fe-N4 active site monatomic catalyst

    CN115301268A

  • Preparation method and application of eutectic solvent type molecularly imprinted polymer based on magnetic metal organic framework material carrier

    CN115368498A

  • Molecularly imprinted polymers

    WO2010085851A1